Primary vaginal carcinoma in genital prolapses: a case report with review of literature - Hota, Basanta M.; Munugala Sravani; Movva, Naimisha; Lokam Geetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Primary vaginal cancer in a case of genital prolapse is a very rare malignancy. The usual age incidence is above 60 years. Likely risk factors and etiology are elderly age, smoking, low immunity, mechanical irritation and inflammation, and persistent infection with oncogenic human papillomavirus. Clinical presentation varies with the stage of the disease. Usually confused with decubitus ulcer in advanced genital prolapse. Histopathology of the biopsy specimen confirms the diagnosis. Though clinically staged imaging is required for better management and prognosis. Management modality depends on the stage, type of malignancy, comorbidity, and patient’s decision. Stage, grade, type of cancer, comorbidity, and adequate management affect the prognosis. Here we present a case of primary vaginal carcinoma in a 71 year old lady with complete genital prolapse simulating decubitus ulcer. The diagnosis was confirmed with histopathology and she was treated with radiotherapy. She died in her home two months after her treatment. The aim of the presentation is (1) Statistical documentation for a rare case and (2) To create awareness of vaginal cancer in a clinically benign-looking decubitus ulcer in genital prolapse.